Walking in virtual reality: Effects on gait biomechanics and the role of speed - Los Angeles, Emanuele (2025)
BACKGROUND: Virtual reality (VR) has gained attention for its potential in gait rehabilitation, offering innovative approaches to improving motor recovery and functional mobility. The impact of VR environments on gait biomechanics remains unclear. Conflicting findings in the literature highlight the need to control for gait speed, a known factor influencing joint kinematics and spatiotemporal parameters. AIM: This study aimed to determine whether VR environments alter lower limb joint angles during overground walking and to what extent these effects are influenced by gait speed. METHODS: Twenty-one healthy participants walked in real-world (RLab) and virtual (VRLab) laboratories at a self-selected speed. Joint angles were analyzed using statistical parametric mapping (SPM) with and without covarying for dimensionless gait speed. A repeated measures ANOVA was used to compare joint angles between conditions. RESULTS: Participants walked slower in VRLab compared to RLab. Significant differences in pelvic, hip, knee, and ankle joint angles were observed across the gait cycle without accounting for speed. However, no significant differences in joint angles were found between the two environments after covarying for gait speed. INTERPRETATION: These findings suggest that the differences in joint angles during VR walking are primarily attributable to slower walking speeds rather than the VR environment. This highlights the importance of controlling for gait speed in VR gait analysis to avoid confounding effects and misinterpretation. These results support VR’s feasibility in gait research and rehabilitation when appropriately controlled for speed.